Skala Perusahaan Sebagai Penentu Keberhasilan Kinerja Keuangan Internal Pada Perusahaan Saham LQ-45 - Tri Purwani; Ana Kadarningsih (LPPM Universitas Sains dan Teknologi Komputer, 2021)
There are three objectives in this study, namely to see the effect of company scale, liquidity and capital structure on internal financial performance. The research population took the financial data of companies or issuers of LQ-45 shares of 56 companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sample used was 36 companies with the criteria for issuing complete financial reports for the 2017-2020 period. Methods of data analysis using quantitative data with the classical assumption test, multiple regression test, hypothesis testing and test the coefficient of determination. All the results from the research show a significant effect but with different directions of the relationship. Company scale and liquidity have a positive effect on the company's internal financial performance, but capital structure has a negative and influence